Intergenerational Communication, Country of Origin Dan Word of Mouth Untuk Memprediksi Ekuitas Merek [Intergenerational Communication, Country of Origin and Word of Mouth for Predicting Brand Equity] - Keni Keni; Widya Octaviani (DeReMa (Development Research of Management): Jurnal Manajemen, 2018)
The purpose of this research are to examine whether intergenerational communication, country of origin, and word of mouth can predict brand equity. The population of this research is smartphone consumers. The sample is of 200 smartphone consumers in Jakarta using online questionnares with the nonprobability sampling technique with convenience sampling. The data analysis used in this study was multiple regression analysis.  The results of this study are intergenerational communication, country of origin and word of mouth are positively and significantly predictors of brand equity. Abstrak dalam Bahasa Indonesia : Penelitian ini dilakukan untuk menganalisis pengaruh komunikasi intergenerasi, country of origin dan word of mouth terhadap ekuitas merek. Populasi dalam penelitian ini adalah para pengguna ponsel pintar di Indonesia. Proses pengambilan data dilakukan dengan menyebarkan kuesioner kepada 200 konsumen ponsel pintar di Jakarta dengan teknik sampling non probabilitas berupa convenience sampling. Setelah data dikumpulkan, data kemudian dianalisis dengan menggunakan metode regresi linear berganda. Berdasarkan hasil analisis data, diperoleh hasil bahwa komunikasi intergenerasi, country of origin and word of mouth memiliki pengaruh positif dan signifikan terhadap ekuitas merek.